Hybrid Ring Microgrid with Coordinated Energy Management Scheme. (2016) - Padayattil, Gibin Mathew; Thobias, Twinkle; Sebastian, Juliya; Thomas, Miranda; Pathirikkat, Gopakumar
Abstract: This paper presents a hybrid ring microgrid and its coordinated control for efficient energy management. The proposed microgrid is fed from both utility grid and renewable sources. When energy generated from renewable sources are sufficient enough to meet load demand, utility grid is disconnected from the former. If surplus energy is generated from renewable sources, it is exported to utility grid. When utility grid fails or suffers any power quality issues, microgrid operates in islanded mode. Proposed microgrid consists of both AC bus as well as DC bus in a ring structure. All renewable sources are to be interconnected to DC buses, which eliminates the necessity of complex synchronization circuitry. Also, the ring structure facilitate better voltage profile and higher reliability to consumers within the microgrid when compared to existing radial microgrids. Topology of the proposed microgrid and its control are discussed in this paper. Case studies are conducted and results are observed in MATLAB/SIMULINK platform.